Amanita Phalloides intoxication - methods of treatment and epidemiology in Lublin voivodeship in last 5 years - Tkaczyk, Jędrzej; Brożyna, Klaudia; Radzka, Agnieszka; Ciechański, Krystian; Tchórz, Michał; Dobryniewska, Wanda (Journal of Education, Health and Sport, 2018)
Introduction: In Poland, mushrooms poisonings, are still quite often, especially in autumn. Each year, in our country 500-1000 cases of mushrooms poisoning are registered, from which 70% are adults, and 30% children. Amanita Phalloides, also known as a ‘death cap’ is one of the most poisonous mushrooms in our climatic zone, and is responsible for ca. 90-95 % of all deadly mushroom poisonings. Aim of the study: is to present an epidemiology of Amanita poisonings in a Lublin voivodeship in a last 5 years, as well as the up to date methods of managing this kind of poisonings. Materials and methods: Data comes from the database of the Department of the Toxicology of Medical University of Lublin. To present the methods of treatment, the analysis of the available publications was made. Results: In years 2013-2018 in a Clinical Department of Toxicology of the Medical University in Lublin, 78 patients were hospitalized because of the mushroom intoxication. 37 (47.5%) of them were male and 41 (52,5%) - women. In 27 patients (34%), the poisoning with Amanita Phalloides was confirmed. The most mushrooms poisonings occurred in 2017 (21). Mushroom poisoning is the most common in summer and autumn - the most cases occured in August, September and October. Discussion: First steps in case of suspecting amatoxins intoxication is to take the clinical history of the patient and start stabilizing measures. To confirm Amanita poisoning, a test that allows to detect α-amanitine in urine can be made. Several drug treatments have been applied in intoxications by amatoxins, from which the biggest role plays sylibin and N-acetylcystein.